FACTORS THAT INFLUENCE EMPLOYEE PERFORMANCE: MOTIVATION, LEADERSHIP, ENVIRONMENT, CULTURE ORGANIZATION, WORK ACHIEVEMENT, COMPETENCE AND COMPENSATION (A STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE STUDIES) - Phong Thanh Nguyen; Andri Yandi; M. Rizky Mahaputra (Dinasti Publisher, 2020)
Previous research or relevant research is very important in a scientific research or article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. From the research theme Motivation Factors, Leadership, Work Environment, Organizational Culture, Work Performance Competence, and Compensation, which affect Employee Performance (A Literature Study of Human Resource Management). hypothesis has been obtained for further research, namely: 1) Work Motivation has a relationship and affects the Employee Performance; 2) Leadership influences Employee Performance; 3) Work environment influences employee performance; 4) Organizational Culture influences Employee Performance; 5) Job Performance influences Employee Performance; 6) Competence influences Employee Performance 7) Compensation influences Employee Performance.